Opening the dynamic infrared sky - Soon, J.; Moore, A.; Kasliwal, M.; Lau, R.; De, K.; Travouillon, T.; Jones, M.; Ofek, E.; Smith, R.; Terebizh, V.; McKenna, D.; Hale, D.; et al. (2018)
© 2018 SPIE. While optical and radio transient surveys have enjoyed a renaissance over the past decade, the dynamic infrared sky remains virtually unexplored from the ground. The infrared is a powerful tool for probing transient events in dusty regions that have high optical extinction, and for detecting the coolest of stars that are bright only at these wavelengths. The fundamental roadblocks in studying the infrared time-domain have been the overwhelmingly bright sky background (250 times brighter than optical) and the narrow field-of-view of infrared cameras (largest is VISTA at 0.6 sq deg). To address these challenges, Palomar Gattini-IR is currently under construction at Palomar Observatory and we propose a further low risk, economical, and agile instrument to be located at Siding Spring Observatory, as well as further instruments which will be located at the high polar regions to take advantage of the low thermal sky emission, particularly in the 2.5 micron region.